2012
DOI: 10.1038/npp.2012.4
|View full text |Cite
|
Sign up to set email alerts
|

Reduced γ-Aminobutyric Acid in Occipital and Anterior Cingulate Cortices in Primary Insomnia: a Link to Major Depressive Disorder?

Abstract: Insomnia is closely related to major depressive disorder (MDD) both cross-sectionally and longitudinally, and as such, offers potential opportunities to refine our understanding of the neurobiology of both sleep and mood disorders. Clinical and basic science data suggest a role for reduced γ-aminobutyric acid (GABA) in both MDD and primary insomnia (PI). Here, we have utilized single-voxel proton magnetic spectroscopy (1H-MRS) at 4 Tesla to examine GABA relative to total creatine (GABA/Cr) in the occipital cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 70 publications
6
91
1
1
Order By: Relevance
“…Despite contradictory evidence, 52 results have largely been interpreted within the context of the hyperarousal hypothesis. For example, increased 45 and decreased 46 GABA in the occipital cortex of patients with insomnia have been reported to be consistent with the hyperarousal model of insomnia. However, sleep regulatory molecules interact with each other in complex ways (described in more detail later), and many of their eff ects are dependent on the milieu of the brain state; that is, they are state-dependent.…”
Section: Molecular Mechanisms Of Sleep and Insomniamentioning
confidence: 63%
“…Despite contradictory evidence, 52 results have largely been interpreted within the context of the hyperarousal hypothesis. For example, increased 45 and decreased 46 GABA in the occipital cortex of patients with insomnia have been reported to be consistent with the hyperarousal model of insomnia. However, sleep regulatory molecules interact with each other in complex ways (described in more detail later), and many of their eff ects are dependent on the milieu of the brain state; that is, they are state-dependent.…”
Section: Molecular Mechanisms Of Sleep and Insomniamentioning
confidence: 63%
“…The primary hypotheses were abnormal GABA/creatine, NAA/creatine and glutamate/creatine levels in the ACC, thalamus and cerebellum. Based on our previous GABA/Cr data obtained from the ACC in primary insomnia [17], we estimated 80% power to detect a difference between groups at α = 0.05, twosided with n = 15 in each group. Cramer-Rao % was used as an estimate of the signal:noise ratio.…”
Section: Statisticsmentioning
confidence: 99%
“…It is now well-established that insomnia is associated with a pattern of 24-h physiological hyperarousal (Bonnet & Arand, 2010). Imaging studies have demonstrated that patients with insomnia have relatively lower levels of cortical c-aminobutyric acid (GABA), an important inhibitory neurotransmitter in the central nervous system (Nofzinger et al, 2004;Plante et al, 2012), and increased glucose metabolism during sleep in areas of the brain that regulate arousal, emotion, and cognition (Nofzinger et al, 2004). This increased hyperarousal has important implications for cardiovascular parameters, including parasympathetic tone present during both wake and sleep (Riemann et al, 2010;Roth, 2007).…”
Section: Insomnia Symptoms and Parasympathetic Tonementioning
confidence: 99%